Composition of public expenditures and macroeconomic performance in the European Union - Jesus Ferreiro; Maribel García del Valle; Carmen Gómez (Intervention. European Journal of Economics and Economic Policies, 2012)
The objective of the paper is to test the existence of a relationship between the composition of public expenditures and the macroeconomic outcomes (GDP rate of growth, and unemployment and inflation rates) of the European Union member states during the period 1995-2007. We study the existence of clusters of countries with similar structures of public expenditure using multiple factorial analysis and principal component analysis techniques, and we compare the macroeconomic outcomes of the clusters obtained using statistics test of equality of means. The outcomes show that there is no evidence of the existence of a relationship between the structures of the public expenditure and the macroeconomic performances. This leads us to conclude that there is no single optimum model of public spending that warrants the best macroeconomic performance
Keywords: C38; H50; O43; O52; 330; European Union; composition of public expenditures; economic performance; productive expenditures; cluster analysis